2022
DOI: 10.1091/mbc.e21-04-0214
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Smi1 in cell wall integrity and glucan synthase Bgs4 localization during fission yeast cytokinesis

Abstract: Cytokinesis is the final step of the cell-division cycle. In fungi, it relies on the coordination of constriction of an actomyosin contractile ring and construction of the septum at the division site. Glucan synthases synthesize glucans, which are the major components in fungal cell walls and division septa. It is known that Rho1 and Rho2 GTPases regulate glucan synthases Bgs1, Bgs4, and Ags1, and Sbg1 and the F-BAR protein Cdc15 play roles in Bgs1 stability and delivery to the plasma membrane. Here we charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The DON production is an essential factor in the virulence of F. asiaticum that was influenced by various factors; ROS is a key enhancement factor for DON production [33,34]. Moreover, the expression of trichothecene cluster genes is essential for DON production [35,36]; Smi1 regulates metabolic process by affecting transcription-associated genes [32]. In this study, compared with wild-type and complement strains, in the FaSmi1 deletion mutant, the trichothecene accumulation was obviously decreased (Figure 5B).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The DON production is an essential factor in the virulence of F. asiaticum that was influenced by various factors; ROS is a key enhancement factor for DON production [33,34]. Moreover, the expression of trichothecene cluster genes is essential for DON production [35,36]; Smi1 regulates metabolic process by affecting transcription-associated genes [32]. In this study, compared with wild-type and complement strains, in the FaSmi1 deletion mutant, the trichothecene accumulation was obviously decreased (Figure 5B).…”
Section: Discussionmentioning
confidence: 58%
“…In addition, we also found that the FaSmi1 deletion mutant exhibits increased tolerance to oxidative stress generated by H 2 O 2 and menadione (Figure 4), and the expression of the catalase genes FaCat6 and FaCcp1 and the superoxide dismutase gene FaMnSOD1 was obviously upregulated in ∆FaSmi1. Moreover, the previous study showed that Smi1 is involved in stress tolerance by affecting the expression level of associated genes [32]. Based on these results, we inferred that the deletion of FaSmi1 leads to upregulation of the oxidative balance-associated genes FaCat6, FaCcp1 and FaMnSOD1, which confers the tolerance ability of the FaSmi1 deletion mutant to oxidative stress.…”
Section: Discussionmentioning
confidence: 62%
“…We focused on genes in the pathways of endocytosis, signal transduction, and fatty acid and glycerol biosynthesis, as they were previously shown to be required for acid tolerance. The SMI1 gene is essential for the cell wall integrity pathway, and the OLE1 and GPP1 genes are required for fatty acid and glycerol biosynthesis (Longo et al 2022 ; Pahlman et al 2001 ; Stukey et al 1990 ). We observed increased expression levels of some genes involved in endocytic processes, such as PAN1 and END3 , cell wall integrity ( SMI1 ), and glycerol biosynthesis ( GPP1 ), under acetic acid treatment in Ent ev16, suggesting their involvement in the acetic acid response (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the specificity of the membrane trafficking pathways altered in the absence of rga4 and rga6 , we also examined the accumulation of Smi1, an intrinsically disordered protein which physically interacts with Bgs4 and promotes the localization of both Bgs1 and Bgs4 to the division site, albeit with greater preference for Bgs4 28,29 . Unlike with Sbg1, Smi1‐mEGFP sum intensity at the division site is reduced in the absence of rga4 and rga6 during late ring constriction, especially upon normalization to division site area, thus indicating that Smi1 delivery does not scale with the enlarged division site in rga4Δrga6Δ mutants (Figure 6D–F).…”
Section: Resultsmentioning
confidence: 99%